TECHNOLOGICAL MODERNITY, BIOPOLITICS, AND THE FRAGMENTED SELF: A FOUCAULDIAN ANALYSIS OF POWER, KNOWLEDGE, AND IDENTITY IN VICTORIAN NOVELS (Contemporary Journal of Social Science Review, 2025)
The Victorian period is often interpreted through the lens of industrial expansion and scientific progress; however, such readings frequently overlook the deeper mechanisms through which power, knowledge, and identity were restructured during the nineteenth century. This study reconceptualizes Victorian literature by examining it within the framework of technological modernity and biopolitical control. Drawing primarily on a Foucauldian understanding of power/knowledge, the research investigates how Victorian novels construct individuals not merely as economic agents but as subjects regulated through disciplinary systems, scientific discourse, and moral normalization.Focusing on novels such as Hard Times and North and South, this study argues that Victorian fiction anticipates modern forms of governance in which bodies, behaviors, and identities are monitored and controlled through institutional mechanisms such as education, industrial labor, and social morality. Rather than viewing Darwinian thought solely as a theory of biological evolution, the study interprets it as part of a broader epistemic shift that enabled the classification, regulation, and normalization of human populations.The research demonstrates that Victorian novels reveal the emergence of what Michel Foucault terms “biopower,” where individuals are subjected to subtle yet pervasive forms of control. At the same time, these texts resist such systems by foregrounding emotional complexity, ethical agency, and individual subjectivity. Ultimately, the study argues that Victorian literature functions as both a reflection of modern disciplinary society and a critique of its mechanisms of control, offering insights into the formation of modern identity.